Brittle/Ductile Deformation of Eclogites: Insights From Numerical Models. (2nd July 2019) - Yamato, P.; Duretz, T.; Angiboust, S.
Abstract: How rocks deform at depth during lithospheric convergence and what are the magnitudes of stresses they experience during burial/exhumation processes constitute fundamental questions for refining our vision of short‐term (i.e., seismicity) and long‐term tectonic processes in the Earth's lithosphere. Field evidence showing the coexistence of both brittle and ductile deformation at high pressure‐low temperature ( HP ‐ LT ) conditions particularly fuels this questioning. We here present 2D numerical models of eclogitic rock deformation by simple shear performed at centimeter scale. To approximate the eclogite paragenesis, we considered the deformed medium as composed of two mineral phases: omphacite and garnet. We run a series of models at 2.0 GPa and 550 °C for different background strain rates (from 10 −14 s −1 to 10 −8 s −1 ) and for different garnet proportions (from 0% to 55%). Results show that whole rock fracturing can occur under HP ‐ LT conditions for strain rates larger than 10 −10 s −1 . This suggests that observation of brittle features in eclogites does not necessarily mean that they underwent extreme strain rate. Care should therefore be taken when linking failure of eclogitic rocks to seismic deformation. We also explore the ranges of parameters where garnet and omphacite are deforming with a different deformation style (i.e., frictional vs viscous) and discuss our results in the light of naturally deformed eclogitic samples. This study illustrates that effective stresses sustained by rocks can be high at these P ‐ T conditions. They reach up to 1 GPa for an entirely fractured eclogite and up to 500 MPa for rocks that contain fractured garnet. Key Points: Evidence of brittle features in eclogites does not necessarily mean that they underwent extreme (seismic) strain rate Deformation style analysis in eclogite samples can provide an estimate of the effective stress sustained by these rocks Effective stress levels sustain by rock can be high (i.e., up to 1.0 GPa at 2.0 GPa and 550 °C)